Linear palmar and plantar melanocytic nevi. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
We describe these melanocytic nevi because we have not found anything like those in the literature, which is mainly devoted to the differential diagnosis between acral nevi and melanoma and the dermoscopic aspects of both (1, 2). The herein reported nevi are melanocytic non palpable nevi characterized by their clinical distribution along the course of dermatoglyphics. Both the two congenital and the two acquired nevi grew in proportion to the growth of the foot. The anatomical site may influence the shape of melanocytic nevi. We know for example that the compression exerted by a fold can reduce the growth of a melanocytic nevus and hemangioma; we also know that the recurrent nevus on scar tends to be distributed linearly ie perpendicularly to the suture line. It is therefore possible that the superficial melanocytic nevi are distributed linearly along the furrows of dermatoglyphics.